High-Dose Gamma Irradiation Reduces Pathogenic Bacteria While Preserving Beneficial Taxa in Indonesian Traditional Food ‘Gudeg’ - Pratama, Indra Mustika; Benita, Ashri Mukti; Hermanto, Feri Eko; Lasmawati, Deudeu; Kadir, Idrus; Sugoro, Irawan (Journal of Tropical Life Science, 2026)
Gudeg, a traditional Indonesian dish, is highly susceptible to microbial spoilage. Irradiation technology can be utilized to extend the shelf life of gudeg while preserving its nutritional value. However, the effects of gamma irradiation on the bacterial abundance in food products have not been widely researched. This study investigated how gamma irradiation influences its bacterial community. Vacuum-packed gudeg was gamma-irradiated in a frozen condition at a dose of 20 kGy, with a dose uniformity ratio (DUR) of 1.08. The resulting microbiome was characterized via 16S rRNA sequencing, using non-irradiated gudeg as a comparison. Gudeg samples were then amplified using the standard 16S rRNA V3-V4 primers. After taxonomic classification, alpha diversity indices—Shannon, Margalef, Chao1, and ACE—were applied to compare species richness and evenness in irradiated and non-irradiated samples. The research results showed that irradiation substantially reduced Proteobacteria, particularly staphylococcal species, while preserving beneficial lactic acid bacteria, such as Weissella sp. The overall diversity slightly decreased, but pathogenic risks diminished, indicating extended shelf stability. These findings suggest gamma irradiation as an effective strategy to enhance gudeg's safety and longevity. Furthermore, they offer insights into broader applications of irradiation for preserving high-moisture, ready-to-eat foods and indicate that sustainable research into the effects of irradiation on spoilage microbes and specific pathogens in various traditional food products is possible.